The Male Mating Strategy of the Ant Formica Subpolita Mayr (Hymenoptera: Formicidae): Swarming, Mating, and Predation Risk - Kevin M. O'Neill (Psyche: A Journal of Entomology)
All-male mating swarms of the ant Formica subpolita were observed at the same site, and sometimes on the same plants, for six consecutive years (1988–1993) in southwestern Montana. The swarms, sometimes numbering thousands of males, occurred above and within shrubs and clumps of tall grasses. Mating occurred on the plant surface below the swarms and lasted for 62 s on average. Females controlled who they mated with and were observed to mate with up to 4 different males, before dispersing from swarm sites. I obtained ~900 records of predation on F. subpolita at swarms. Twenty-one species of predator were observed, the foremost of which were the robber fly Efferia staminea and the spider Dictyna coloradensis. With the exception of prey of the digger wasp Aphilanthops subfrigidus, which prey only on females, prey records were overwhelmingly male-biased. Results are compared to observations on other species of ants, especially those in the genus Pogonomyrmex.